Back Cover: Flow‐Through Synthesis on Teflon‐Patterned Paper To Produce Peptide Arrays for Cell‐Based Assays (Angew. Chem. Int. Ed. 25/2014). Issue 25 (28th April 2014) - Deiss, Frédérique; Matochko, Wadim L.; Govindasamy, Natasha; Lin, Edith Y.; Derda, Ratmir
<x xml:space="preserve">Abstract</x> Teflon‐patterned paper that can be used for multistep organic synthesis and then used in cell‐based assays has been developed. In their Communication on page 6374 ff., R. Derda and co‐workers describe the deposition of Teflon onto paper to create solvent‐resistant barriers. The reagents confined by the pattern flow through the layer(s) of paper, thus permitting parallel flow‐through syntheses of 96 peptides on one sheet of paper to produce arrays that can be used for cell‐based assays.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>